Antagonizing IL-6 receptor restores pancreatic tissue resident NK cells activation and ameliorates pancreatic injury in the mouse model of MASH - Amer, Johnny; Arra, Diana Abu; Salhab, Ahmad; Kayed, Faris; Maali, Muneer; Shweiki, Raghad; Ghanim, Mustafa (Frontiers in Pharmacology, 2025)
Background and aimMetabolic-associated steatohepatitis (MASH) and pancreatic inflammation are key complications of obesity-related metabolic syndrome. Elevated IL-6; a proinflammatory cytokine, contributes to liver steatosis and pancreatic β-islet cells dysfunction. This study explores pancreatic tissue-resident (tr)NK cells IL-6 receptor (IL-6R) in pancreatic injury in a murine MASH model.MethodologyMASH models were established using male Ob/Ob mice fed a high-fat diet (Ob/ObHFD; 60.3% kcal from fat) for 4 weeks and using immunocompromised NOD-SCID IL2rγnull (NSG) mice fed with HFD for 16 weeks and i.v. injected with 10 × 106 pancreatic trNK and treated with IL-6R antagonizing antibody on week 12. Biochemical assays assessed serum ALT, AST, lipids, glucose, and insulin levels. Pancreatic injury was analyzed through mRNA expression of Reg1, Reg3, oxidative stress marker of tissue malondialdehyde (MDA) and β−islet cells’ proliferation and apoptosis. Fibrotic markers of α-SMA, Collagen-I, and Fibronectin were assessed via RT-PCR and trNK cell activation (CD107a, NKp46, IFN-γ) were assessed by flow cytometry.ResultsOb/ObHFD mice exhibited increased serum cholesterol, triglycerides, fasting blood glucose, and liver injury enzymes. Markers of pancreatic injury of Reg1/Reg3 and pancreatic MDA with β−islet cells apoptosis were significantly elevated compared to littermates’ control. These results were accompanied by a decline in trNK counts and activations (P < 0.05). In an adoptive transfer model, NSG mice fed with HFD and transplanted with trNK cells from Ob/ObHFD donors (expressing high IL-6) exhibited similar pancreatic injury markers, whereas those receiving trNK cells from Ob/ObHFD mice pre-treated with an IL-6R antagonist showed marked reductions in Reg1/Reg3 (∼2-fold), MDA (∼1.77-fold), and β-islet cells apoptosis (∼2.2-fold). Moreover, phenotypic characterization of the NSG mice fed an HFD transplanted with IL-6R antagonizing antibody showed an increase in the NK cell activation marker CD107a (∼2.3-fold) and amelioration in pancreatic fibrotic profile of α-SMA mRNA expressions of 1.6 -fold when compared to its counterparts.ConclusionOur data highlights the importance of IL-6R modulation on trNK cells in remodeling pancreatic tissue after liver injury, emphasizing the liver-pancreas axis as a therapeutic target to prevent pancreatic damage, β-islet cells dysfunction and fibrosis and reduce the risk of diabetes and metabolic syndrome.